Species of Scina Prestandrea, 1833 (Amphipoda, Hyperiidea, Scinidae) from western Mexico with the description of a new species from the Gulf of California - Gasca, Rebeca; Hendrickx, Michel E. (Zootaxa, 2020)
Only a few previous surveys of the deep-water planktonic fauna have been accomplished off western Mexico, in particular in the Gulf of California. Samples of pelagic amphipods were obtained between surface and as deep as 2394 m using different gear during an extensive survey in this area. Among these samples, nine species of the genus Scina were recognized, including 78 specimens: 27 males and 51 females. The genus Scina inhabits mesopelagic waters at depths over 200 m, a community that remains largely unknown. The material examined includes a new species, the first reported from the Gulf of California, which is described and compared with its closest congeners, S. setigera Wagler, 1926 and S. parasetigera Zeidler, 1990. These three species share the presence of a long bristle on the base of the dactylus of pereopods 5 and 6. Scina sp. nov. differs from these other two species mainly by: 1) the shape and proportions of pereiopods 1–7; 2) the presence of three inner spiniform elements on uropod 1; 3) the insertion of the exopod on distal 1/3 of uropods. Of the remaining species collected during the survey S. borealis was by far the most abundant and widely distributed, followed by S. wolterecki and S. marginata. The other five species, S. curvidactyla, S. nana, S. pacifica, S. setigera, and S. submarginata, were represented by one or two specimens only. Co-occurence of species of Scina in samples was low with a maximum of four species in a single sample, all associated with S. borealis, the most common species. The distribution of Scina species collected during this survey is briefly discussed.